2017
DOI: 10.1108/ejtd-04-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors of justice and culture leading to organizational identification in merger and acquisition

Abstract: Purpose This paper aims to examine the influence of two organizational factors, namely, organizational justice and organizational culture, on organizational identification as perceived by employees following merger and acquisition (M&A) in Malaysia. Design/methodology/approach The study, which adopts the Social Identity Theory as its theoretical foundation, was conducted among employees from selected Malaysian organizations that had undergone M&A from 2009 to 2016. Data were obtained from 302 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Given the interplay between leader ML, symmetrical internal communication, positive emotional culture, and organizational identification as hypothesized, the study also proposes the mediating role of positive emotional culture, which can potentially explain how communication in the organization influences employee identification. In particular, since leader ML and organizational-level symmetrical communication could both predict a positive emotional culture and organizational identification, and given the innate linkage between culture and identification (Ismail & Baki, 2017; Ravasi & Schultz, 2006), the study suggests that positive emotional culture could mediate the effects of leader ML and symmetrical internal communication on organizational identification. In other words, leaders’ use of meaning making, empathetic, and direction-giving language and an employee-centered internal communication system jointly create a positive emotional culture, which can in turn, boost employee organizational identification.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Given the interplay between leader ML, symmetrical internal communication, positive emotional culture, and organizational identification as hypothesized, the study also proposes the mediating role of positive emotional culture, which can potentially explain how communication in the organization influences employee identification. In particular, since leader ML and organizational-level symmetrical communication could both predict a positive emotional culture and organizational identification, and given the innate linkage between culture and identification (Ismail & Baki, 2017; Ravasi & Schultz, 2006), the study suggests that positive emotional culture could mediate the effects of leader ML and symmetrical internal communication on organizational identification. In other words, leaders’ use of meaning making, empathetic, and direction-giving language and an employee-centered internal communication system jointly create a positive emotional culture, which can in turn, boost employee organizational identification.…”
Section: Literature Reviewmentioning
confidence: 79%
“…A longitudinal study of students from a recently merged university, for instance, revealed the perceived fairness of the merger process positively predicted students’ post-merger identification, and the positive effect of fairness increased over time (Gleibs, Mummendey, & Noack, 2008). Another study of employees from organizations that had undergone recent mergers and acquisitions (M&A) revealed a similar importance of justice, with perceptions of interactional justice (e.g., being treated by managers with kindness, respect, and dignity regarding job decisions) having a positive effect on employees’ OI following the M&A (Ismail & Baki, 2017).…”
Section: A Review Of Oi Antecedents From Four Research Categoriesmentioning
confidence: 99%
“…It may be tempting to take administrative decisions that may be in favor of certain employees regarding the distribution of organizational outputs within the framework of powers (Abekah-Nkrumah & Atinga, 2013). However, the distributive justice perception becomes valid only when the "win-win" situation occurs (Ismail & Baki, 2017). Therefore, in a business life, all employees compare the benefits they provide to the organization with the salary they receive, and in some cases, it improves the perception of injustice, and this affects the employees' perceptions of justice (Hao et al, 2016).…”
Section: Organizational Justicementioning
confidence: 99%